The lower Krishna Basin trajectory: relationships between basin development and downstream environmental degradation - Venot, Jean-Philippe; Sharma, Bharat R.; Rao, K.V.G.K. (International Water Management Institute, 2008)
Basin water development and rural dynamics in the Krishna Basin have led to a degradation of downstream ecosystems manifesting itself by salinizing soil and groundwater, increasing pollution, disappearing mangroves and desiccating wetlands. Reversing this evolution requires the formal recognition of the environment as a water user in its own right and the implementation of an environmental water provision. This provision should be based on a two-tier allocation system with assured discharges in the irrigation canals of the delta and to the ocean. This will lead to further commitment of water resources but this is needed to reconcile the social, economic and environmental objectives of a sustainable development. Other measures facilitating integrated natural resources management from the local to the basin level are needed too.